Analisis manajemen risiko pada e-learning SMAN 1 Ambarawa dengan menggunakan ISO 31000:2018 - Hesni Joice Isabel Br Isabel; Andeka Rocky Tanaamah; Akhmad Muttamaqin (AITI, 2026)
This study aims to identify the main risks faced by SMAN 1 Ambarawa, evaluate the extent to which these risks are currently managed, and develop strategic recommendations to overcome existing obstacles and potential future risks. The framework used in this research is ISO 31000:2018 risk management framework. This research employs a qualitative approach, particularly through interviews with relevant stakeholders, to identify and analyze the problems that may affect school operations. Through this qualitative approach, various existing and potential risks can be systematically identified and analyzed. The identified risks are then analyzed and categorized into three levels: low, medium, and high risk, based on their likelihood and impact. Furthermore, appropriate risk treatment strategies are proposed for each identified risk to minimize negative consequences and improve institutional preparedness. The results of this study provide practical recommendations for SMAN 1 Ambarawa in managing risks and in developing preventive strategies to reduce the possibility of future disruptions in school activities and management processes.